Disc Shaping Cutters and Their Features When Cutting Tooth Wheels (Texas Journal of Engineering and Technology, 2022)
The article covers the analysis of calculation data for tooth wheels of various sizes and their influence on the service life of disk shaping cutters, and provides algorithm for constructing the line of features of the absence of gear interference.